The Impact of DER, TATO, CR, & EPS on Stock Prices Alongside DPR as a Mediation Variable (Case Study of the Industrial Sector on the Indonesian Stock Exchange 2020-2022) - Alvira Lutfiah (Program Studi Akuntansi FPEB UPI, 2024)
This study aims to determine the effect of DER, TATTOO, CR and EPS ratios on stock prices with Dividend Payout Ratio as a mediating variable in consumer goods companies for the 2015-2019 period. The population used in this study is industrial sector companies on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. This type of research is quantitative. Secondary data and purposive sampling are used in data retrieval and sampling techniques with multiple linear analysis. Using SPSS 23. The results of the study were that DER, TATTOO, CR, and EPS had no effect on DPR. DER, TATO, and CR affect share price, while EPS and DPR have no influence on share price. The House does not mediate DER, TATTOO, CR, and EPS against the Share Price.